Association of the Vaccinia Virus A11 Protein with the Endoplasmic Reticulum and Crescent Precursors of Immature Virions - Maruri-Avidal, Liliana (American Society for Microbiology, 2013)
The apparent de novo formation of viral membranes within cytoplasmic factories is a mysterious, poorly understood first step in poxvirus morphogenesis. Genetic studies identified several viral proteins essential for membrane formation and the assembly of immature virus particles. Their repression results in abortive replication with the accumulation of dense masses of viroplasm. In the present study, we further characterized one of these proteins, A11, and investigated its association with cellular and viral membranes under normal and abortive replication conditions. We discovered that A11 colocalized in cytoplasmic factories with the endoplasmic reticulum (ER) and L2, another viral protein required for morphogenesis. Confocal microscopy and subcellular fractionation indicated that A11 was not membrane associated in uninfected cells, whereas L2 still colocalized with the ER. Cell-free transcription and translation experiments indicated that both A11 and L2 are tail-anchored proteins that associate posttranslationally with membranes and likely require specific cytoplasmic targeting chaperones. Transmission electron microscopy indicated that A11, like L2, associated with crescent membranes and immature virions during normal infection and with vesicles and tubules near masses of dense viroplasm during abortive infection in the absence of the A17 or A14 protein component of viral membranes. When the synthesis of A11 was repressed, “empty” immature-virion-like structures formed in addition to masses of viroplasm. The immature-virion-like structures were labeled with antibodies to A17 and to the D13 scaffold protein and were closely associated with calnexin-labeled ER. These studies revealed similarities and differences between A11 and L2, both of which may be involved in the recruitment of the ER for virus assembly.